Efecto del megacariocito sobre el estroma medular - Lev, Paola Roxana (2022)
Bone marrow stromal cells provide a proper environment for the development of hematologic lineages. The incorporation of different stromal cells to in vitro culture systems would be an attractive model to study megakaryopoiesis and thrombopoiesis. Our objective was to evaluate the participation of different types of stromal cells on in vitro megakaryopoiesis, thrombopoiesis and megakaryocyte (MK) survival. CD34-positive progenitors from umbilical cord blood were differentiated into MK precursors and then co-cultured with umbilical vein endothelial cells (HUVEC), bone marrow mesenchymal stem cells (MSC), skin fibroblasts (SF) (all human) or mouse fibroblast cell line (L929). The number of MKs (CD61-positive cells) was increased in the presence HUVEC and SF while L929 cells decreased total and mature MKs count. Concerning thrombopoiesis, HUVEC increased proplatelet (PP) producing MKs, while MSC, L929 and SF had the opposite effect (immunofluorescence staining and microscopic analysis). MK survival was enhanced in MSC and SF co-cultures, as assessed by pyknotic nuclei evaluation. However, HUVEC and L929 did not prevent apoptosis of MKs. Overall, our results indicate that each cell type performs distinct functions, which differentially modulate MK growth and platelet production, highlighting the relevance of considering the influence of stromal cells in MK research.